Media Flashcard Berbasis Augmented Reality untuk Meningkatkan Kognitif Materi Sistem Pernapasan Manusia pada Siswa Kelas V Sekolah Dasar - Putri, Devi Aninda; Supriyono, Supriyono; Yani, Ahmad (JOEAI (Journal of Education and Instruction), 2026)
The objective of this study was to determine the validity and effectiveness of implementing augmented reality-based flashcards to improve cognitive learning outcomes in fifth-grade elementary school students. This study used the Borg and Gall Research and Development (R&D) model. The study population consisted of fifth-grade elementary school students in Sumberpucung District, selected using a probability sampling technique with cluster random sampling. Quantitative data were collected from validation sheets and learning outcome test sheets. The augmented reality-based flashcards on the human respiratory system were produced as cards equipped with barcodes, which were scanned with a device to display an augmented reality experience corresponding to the material. Instructions for use were also provided. Experts declared the augmented reality-based flashcards valid as a learning tool for fifth-grade elementary school students. In conclusion, augmented reality-based flashcards were effective in improving cognitive learning outcomes in fifth-grade elementary school students on the human respiratory system. The effectiveness of the media can be seen from the results of the difference test between the experimental and control groups.   Keywords: Flashcards, Augmented Reality, Cognitive Learning Outcomes, Human Respiratory System Material